2021
DOI: 10.3390/biology10121262
|View full text |Cite
|
Sign up to set email alerts
|

Syrah Grape Skin Residues Has Potential as Source of Antioxidant and Anti-Microbial Bioactive Compounds

Abstract: In this study, we evaluated the effects of ultrasound-assisted extraction (UAE) under different time-temperature conditions on the content of bioactive compounds, antioxidant and antimicrobial activities of Syrah grape skin residue. The application of UAE showed a positive effect on the extraction of total flavonoids, and a negative effect on total polyphenols. The temperature of 40 °C and 60 °C without the UAE caused an increase of 260% and 287% of the total polyphenols, respectively. Nineteen individually bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The UESC sample presented flavonoid concentration 1.7 times higher than its control (ESC). The authors De Andrade et al [24] indicate that the pretreatment of grape skin samples with ultrasound improves the yield of FT. This can be justified because the ultrasound waves stimulate the formation of small bubbles subjected to rapid compression and expansion, causing rapid local increase in temperature and pressure, which facilitates the solubilization of compounds present in the matrix [26].…”
Section: Antioxidant Profile Of Green Propolis Extracts (Total Phenol...mentioning
confidence: 99%
See 1 more Smart Citation
“…The UESC sample presented flavonoid concentration 1.7 times higher than its control (ESC). The authors De Andrade et al [24] indicate that the pretreatment of grape skin samples with ultrasound improves the yield of FT. This can be justified because the ultrasound waves stimulate the formation of small bubbles subjected to rapid compression and expansion, causing rapid local increase in temperature and pressure, which facilitates the solubilization of compounds present in the matrix [26].…”
Section: Antioxidant Profile Of Green Propolis Extracts (Total Phenol...mentioning
confidence: 99%
“…Efforts have been made to improve conventional methods, applying alternatives that improve the yield and reduce the time and costs of the extraction step [24,25]. One alternative is the increasingly common use of sonication as a pretreatment in extraction processes of bioactive compounds in plant matrices [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proved that these health-promoting compounds are highly accumulated in the skin, seeds, stems, and leaves of grapes [94,171]. Several studies have identified various phenolic compounds in grape skins, including phenolic acids, stilbenes, flavanols, flavonols, and anthocyanins [91,95,98], namely malvidin-3,5-di-O-glucoside and the flavonol quercetin-β-D-glucoside [172]. Regarding the nutritional value of grape pomace, it can be observed that red grape varieties are rich in dietary fibers, consisting mainly of lignin, cellulose, and hemicellulose [93].…”
Section: Grapementioning
confidence: 99%
“…An alternative to reduce the amount of unexploited waste with a negative impact on the environment is represented by their valorisation through green extraction, isolation and purification of bioactive compounds in order to obtain added value products, useful in the prevention and treatment of various maladies. Numerous studies have shown that vegetable waste is an important and low-cost source of primary and secondary metabolites with medicinal and nutritional value, such as phenolic compounds (phenolic acids [20,38,67,76], flavonoids [14,18,20,22,23,34,42,56,65,71,74], anthocyanins [20,21,35,57,71], vitamins (vitamin A [25], vitamin E [21], vitamin D [25], vitamin C [21,25,65,74], amino acids [25], alkaloids [11,18], glucosinolates [23], fatty acids [21], poly-saccharides [55], terpenes [14,38,57,74].…”
Section: Current Strategies For Vegetal Waste Valorisationmentioning
confidence: 99%